HIGH-ENERGY MILLING OF MAGNESIUM WITH ZEOLITE FOR HYDROGEN STORAGE - Adhira Satria Pratama; Gumawa Windu Manggada; Magdy Abdelghany Elsayed; Shixue Zhou (DISTILAT: Jurnal Teknologi Separasi, 2024)
Magnesium has received great attention as a potential material for hydrogen storage due to its environmental friendliness, high gravimetric hydrogen storage capacity, and low cost. However, the material's effectiveness is limited by its high thermodynamic stability, which makes hydrogen desorption challenging, and low reaction kinetics, which slows the rate of hydrogen absorption and desorption. To enhance the performance of magnesium as a hydrogen storage material, this work innovatively aims to examine the impact of time and high energy milling speed on particle size as well as the milling aid effect of zeolite 5A. Experiment results showed that after ball milling with 4 h milling time and 270 r/min milling speed, the size of magnesium crystallites calculated from XRD data is in the range of 32.8-49.3 nm, while the size before ball milling was 72.7 nm. The kinetic measurement results showed that the Mg+10 wt.% zeolite 5A+10 wt.% Ni sample with 4 h milling time and 270 r/min milling speed at 330°C and 2.5 MPa had the best absorption and desorption capacity of 4.14 wt.% and 3.91 wt.%, respectively, in less than 25 min. The synergistic effect of milling time, milling speed, and the addition of zeolite 5A with Ni has a significant role in reducing the size of Mg particles, which affects the absorption and desorption performance of magnesium.